„Oni się tylko bawią” – czy tylko? Kontrowersje wokół hasła nauka przez zabawę - Jolanta Zwiernik (Problemy Wczesnej Edukacji)
The content of this article are considerations relating to the slogan of play-based-learning. In the first part of the text, referring to the classical definition by Johan Huizinga, the characteristics of play and its functions are presented (Hurlock, Brzezinska), the definition of learning by Teresa Bauman is quoted, and the activity of learning understood as a creative process is discussed (Stasiakiewicz). The second part of the text analyzes two theoretical positions (Moyles, Edwards) and relates their fragments to examples from educational practice. In the conclusion, the author returns to the initial thesis of the article stating that play, learning and work are three different areas of human activity and it is good to preserve their separateness for the benefit of each of them.